Development Alternatives. Issue 4 (19th June 2015) - Radcliffe, Sarah A.; Arsel, Murat
ABSTRACT Development alternatives arguably emerge out of practices, negotiations and critiques of dominant development narratives and paradigms. Critical Development Studies' (CDS) practices of insightful critique and a willingness to challenge hegemonic paradigms are alive and well. Yet this article argues that CDS could fruitfully pay attention to emergent issues that have yet to receive sustained analysis and critique. The article focuses on three very different registers of development futures: evolutionary and resilience‐based thinking; post‐neoliberal experiments in Latin America; and the challenge of social heterogeneity. After summarizing the issues involved with respect to each topic, the article suggests some aspects that require further research and debate.